Ag-loaded cerium-zirconium solid solution oxide nano-fibrous webs and their catalytic activity for soot and CO oxidation. (15th January 2018) - Lee, Chanmin; Jeon, Yukwon; Kim, Taehyen; Tou, Akihiro; Park, Joo-Il; Einaga, Hisahiro; Shul, Yong-Gun
Graphical abstract: Highlights: Ce-ZrO2 solid-solution oxide fibrous webs were synthesized by electrospinning. Ag particles were deposited to improve catalytic activity. Ag/Ce0.67 Zr0.33 O2 exhibited superior catalytic activity to other sample. Redox property of Ag and enhanced surface areas improved the catalytic oxidation. Abstract: The catalytic combustion of soot and CO is one of the key technologies required to meet rigorous emission standards. Recently, solid solution materials have been employed in heterogeneous catalysts because of their remarkable intrinsic activities and good stabilities. However, the low number of contact points between soot particles and the catalyst remains a challenge to enhancing catalytic performance. Thus, we herein report the preparation of Ce-ZrO2 solid solution nano-fibrous web catalysts with a hierarchical structure using an electrospinning method, where Ag particles were loaded onto the surface of the Ce-ZrO2 webs. X-ray diffraction, scanning transmission electron microscopy, and energy dispersive spectroscopic studies allowed us to investigate the morphological and crystal structures of the prepared Ce-ZrO2 and Ag/Ce-ZrO2 web catalysts. Moreover, the relationship between the Ce/Zr ratio and activated oxygen is discussed based on X-ray photoelectron spectroscopy results. Following the catalytic oxidation of soot and CO using our novel materials, we found that the Ce0.67 Zr0.33 O2 web exhibited higher catalytic activities than the Ce0.5 Zr0.5 O2 and Ce0.33 Zr0.67 O2 webs, respectively. In addition, Ag/Ce0.67 Zr0.33 O2 exhibited enhanced catalytic activity compared with the pristine Ce0.67 Zr0.33 O2 for the oxidation of both soot (e.g., 500 °C vs. 544 °C at 50% conversion) and CO (e.g., 282 °C vs. 408 °C at 50% conversion). It therefore appeared that our proposed Ce-ZrO2 solid solution nano-fibrous web catalysts bearing Ag particles exhibited superior redox properties and enhanced surface areas, and as such, are promising candidates for use in the oxidation of both soot and CO.